Antibiotic resistance situation in Dhaka, Bangladesh: a review - Rahman, M. Rashedur; Islam, Fargana; Rahman, M. Ashikur; Bashar, Shammi Binte; Rifat, Rakibul Hasan; Saha, Bidhan Chandro; Paran, M. Shah (International Journal of Basic & Clinical Pharmacology, 2021)
Antibiotic resistance is global trouble and in the megacities, it is causing more rapidly due to the misuse and overuse of antibiotics. This systematic evaluation used to be carried out to summarize the contemporary day kingdom of affairs of antibiotic resistance in Dhaka, to emerge as aware of gaps in close observation, and to prink tips primarily based on honesty and surely on the findings. Google scholar, PubMed, and Bangladeshi journals online have been searched for the use of applicable key phrases to select articles connected to antibiotic resistance in Dhaka, Bangladesh published between 2004 to 2020. The resistance of a bacterium to a given drug was once added as the median resistance and interquartile fluctuate. Forty-one articles have been blanketed in this systematic review. Antimicrobial susceptibility trying out used to be once as quickly as carried out via disk diffusion approach in 97.56% of studies, at the equal time as the clinical and laboratory standards institute suggestions had been accompanied in 92.68%. Data concerning the susceptibility attempting out method and furnish of sickness (hospital/community) had been absent in 12.19%, 10.52%, and 90.24% of the research, respectively. An excessive prevalence of resistance used to be detected in most examined pathogens, and many of the normal first-line pills have been the most importantly ineffective. Resistance to carbapenems was once low in most cases. An excessive incidence of resistance to most antibiotics used to be detected, alongside necessary gaps in surveillance and facts gaps in the methodological data of the show up to be up.